In-season internal training load quantification of an under-17 European male soccer team: Starters versus Non-starters - Oliveira, Rafael (2021)
The aim of this study was to compare internal training load (ITL) of starters versus non-starters from the same under-17 soccer team. Rated of perceived exertion was collected and then multiplied by training or match duration (s-RPE) from twenty-three soccer players. The study analysed a total of 12 matches and 44 training sessions during the in-season with ANOVA with repeated measures. The main results showed that training duration presented significant differences between starters and non-starters for match-day minus 5 (MD-5, 80.6 vs 90.7 min, p=0.000) and match-day (MD, 64.2 vs 52.7 min, p=0.036), respectively. Regarding s-RPE, there were significant differences between starters and non-starters for MD-5 (442.4 vs 581.8 a.u., p=0.000) and MD (515.9 vs 366.1 a.u., p=0.000), respectively. This study present relevant additional ITL data for nonstarters in order to become a “starter player”